Atypical presentation of appendicitis. (10th November 2016) - Beaumont, Oliver; Miller, Robert; Guy, Richard
Abstract : A woman aged 64 years presented as an emergency with a mass in the right iliac fossa, clinically within the abdominal wall, but an otherwise soft abdomen. Systemically, she was quite well with normal vital signs. Blood tests revealed raised inflammatory markers, and an abdominal CT scan demonstrated a perforated appendix with associated large subcutaneous abscess. This represents a rare presentation of a common condition, demonstrating how appendicitis can still be a challenging problem for the clinician. The patient underwent incision and drainage of the abscess, resulting in the formation of an enterocutaneous fistula (ECF). This was managed with enteral nutritional support, wound dressings and antibiotics. Following normal CT imaging, an ileocaecal resection was planned in the expectation that the ECF would persist. The operation was postponed due to intercurrent illness, during which time her symptoms and the ECF fully resolved.